2019
DOI: 10.5037/jomr.2020.11103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Depth of Clinically Detected Approximal Caries Lesions Using Digital Imaging Fiber-Optic Transillumination in Comparison to Periapical Radiographs

Abstract: The aim of present prospective clinical trial was to assess the depth of clinically detected approximal caries lesions using digital imaging fiber-optic transillumination in comparison to periapical radiographs. Material and Methods: One calibrated examiner diagnosed 31 approximal carious lesions in 10 patients with a mean age of 21.8 (SD 1.1) years. The lesions were assessed using digital imaging fiber-optic transillumination (DIFOTI) and digital periapical radiographs (PA). Depending on the depth of the lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Dentists generally utilize intraoral radiography to identify and diagnose dental caries. Lasers, specifically fiber-optic transillumination and near-infrared light transillumination, have been recently introduced for non-ionizing caries detection ( Antipoviene et al, 2020 , Litzenburger et al, 2020 , Marmaneu-menero et al, 2020 , Strassler and Pitel, 2016 ). Since PAI employs laser or other non-ionizing radiation sources, it has the potential to be advanced as an alternative imaging modality for the detection of oral diseases, including caries.…”
Section: Discussionmentioning
confidence: 99%
“…Dentists generally utilize intraoral radiography to identify and diagnose dental caries. Lasers, specifically fiber-optic transillumination and near-infrared light transillumination, have been recently introduced for non-ionizing caries detection ( Antipoviene et al, 2020 , Litzenburger et al, 2020 , Marmaneu-menero et al, 2020 , Strassler and Pitel, 2016 ). Since PAI employs laser or other non-ionizing radiation sources, it has the potential to be advanced as an alternative imaging modality for the detection of oral diseases, including caries.…”
Section: Discussionmentioning
confidence: 99%
“…Точно так же остаются нерешенными вопросы о глубине проникновения инфракрасного излучения в зубы и возможная индуцированная инфракрасная флуоресценция, вызванная облучением кариозной зоны инфракрасным светом с длиной волны 830 нм [ 15 ] . Область применения волоконно-оптической трансиллюминации довольно широка, она включает использование в качестве дополнительного диагностического средства для диагностики межпроксимального и окклюзионного кариеса, обнаружения зубных отложений, оценки окрашенных краев композитных пломб, переломов и трещин в зубах, для освещения доступа и устьев корневых каналов во время эндодонтического лечения, в качестве инструмента для улучшенной оценки повреждений мягких тканей, для оценки цельнокерамических реставраций, чтобы исключить любые переломы перед цементированием, для клинической оценки трещин и линий деформации цельнокерамических реставраций, реставраций и естественных зубов, а также для оценки глубины внешнего окрашивания для определения соответствующих рекомендаций по лечению [ 17 ] .…”
Section: диагностика кариесаunclassified
“…The DC showed good potential for the detection of proximal caries clinically. Recent published clinical studies have shown that DC has a higher sensitivity for enamel caries while BWR gave the best prediction of proximal dentine caries 20,21 . Alamoudi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent published clinical studies have shown that DC has a higher sensitivity for enamel caries while BWR gave the best prediction of proximal dentine caries. 20,21 Alamoudi et al performed a cross-sectional analysis of diagnosing cavitated proximal lesions in primary molars and concluded that DC showed higher sensitivity and better accuracy than BWR. 22 However, the significant heterogeneity in the study designs and the reference standards make it difficult to affirm that NIRLT could substitute X-rays in the auxiliary diagnosis of carious lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation